Derivation of the word Zhahara and the context of its meaning in the Qur'an: Morphosemantic Analysis - Royani Ridloul Afifah (Universitas Muhammadiyah Enrekang, 2024)
The purpose of this study is to describe the derivation of the word ظهر in the Quran, and also describe the context of its meaning in the Quran. This research is a qualitative research with the research design in the form of a literature study, the data collection technique is listening-note. The method uses the distribution or distributive method. The result of this study is that the derivation of the word ظهر in the Al Quran was found to be 58 data in total, but the study took 14 data to be analyzed to the maximum, because many data are of the same type. Derivatives of the word ظهر have 11 forms, with 8 wazn, namely: ظهر: فعل ماض, أظهر : فعل ماض زيادة بحرف, ظهير : مصدر قياسى , يظهر: فعل مضارع ,تظاهر : فعل مضارع زيادة بحرفين ,ظهور : مصدر قياسى, ظاهر : اسم فاعل , ظهر : مصدر قياسى From the derivation of the word ظهر in the context of its meaning, several meanings of the word are found, namely: تظاهر; Please help, ظهور; back,, يظهر; powerful, ظاهر; born, ظهر; apparently, ظهْر; surface , تظهر; the time of Zuhr and يظاهر; zihar.